(untitled) (Research, Society and Development, 2021)
Aim: The aim of the present study is to report a clinical case of a patient with intraoral lipoma in the right floor of the mouth area. Methodology: It consists of an qualitative, observational, descriptive and retrospective study, of the case report type, about an intraoral lipoma, showing clinical and histopathological characteristics of this lesion. Case Report: Female patient, 63 years old, hypertensive, diabetic, presented to the service of maxillofacial surgery and traumatology at Hospital Getúlio Vargas, complaining of increased volume in the right floor of the mouth area. There was an increase in extraoral volume in the submental and intraoral regions on the right oral floor, with the same coloration of the mucosa, painless on palpation and flaccid consistency. After ultrasound examination, lipomatous tissue was found and excisional biopsy of the lesion was performed under general anesthesia, with an intraoral approach. Histopathological examination confirmed the diagnosis of lipoma. Discussion: Lipomas are often misdiagnosed, being confused with liposarcomas. This occurs since liposarcomas, rare lipomatous lesions, have an atypical clinical presentation. Thus, in several cases, the patient’s prognosis may be compromised. Conclusion: In short, lipomas are benign neoplasms of an adipose nature that are atypical in the oral cavity and are not associated with pain. Histopathological examination is essential to differentiate lipoma from similar tumors, although microscopic variants generally do not affect the prognosis.